Aqeedah Values of Ahli Sunnah Waljama’ah in “Hikayat Tengkorak Kering”: A Content Analysis - Harapandi Dahri (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
Aqeedah, fiqh, and akhlaq are the three main pillars in carrying out the religion that the Prophet has brought to the earth so that human beings can know their destiny perfectly. This matter has been recorded in the hadith of Jibril, which is a hadith that explains the arrival of the Angel Jibril to teach the pillars of religion to Muslims. The scholars describing the values of the three main teachings have various ways and methods. One of them is Haji Abdullah bin Haji Muhammad Sa'ed bin Haji Muhammad Arsyad who used the story entitled